Evidence for restricted muscle blood flow during speed skating - Foster, C.; Rundell, K. W.; Snyder, A. C.; Stray-Gundersen, J.; Kemkers, G.; Thometz, N.; Broker, J.; Knapp, E. (Medicine & Science in Sports & Exercise, 1999)
The results were supported by greater desaturation with smaller knee angles during static exercise and by greater desaturation and accelerated blood lactate accumulation during on-ice speed skating in the low vs high position. The results of this study support the hypothesis that physiological responses during speed skating are dominated by restriction of blood flow, attributable either to high intramuscular forces, the long duty cycle of the skating stroke, or both.